Understanding and Translating Chinese Martial Arts - Jiao, Dan.; Li, Defeng; Meng, Lingwei; Peng, Yuhong (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
The present book features some introductory discussions on martial arts for the international audience and highlights in brief the complexities of translating the genre into English, often from a comparative literature perspective. Martial arts, also known as Kungfu or Wushu, refer to different families of Chinese fighting styles over many centuries. Martial arts fiction, or Wuxia literature, is a unique genre that depicts adventures of martial artists in ancient China. Understanding martial arts and the Chinese culture and philosophy behind them creates an intriguing experience, particularly, for non-Chinese readers; translating the literature into English poses unparalleled challenges for translators not only because of the culture embedded in it but also the fascinating martial arts moves and captivating names of many characters therein.
Kungfu - Musings on the Philosophical background of Chinese Martial Arts -- Cross-cultural Communication of Chinese Wushu in an Omnimedia Context: Problems and Solutions -- The Mythology of Chinese Martial Arts Tourism$1!+:(BA Case study of the Shaolin Temple on Multiple Dimensions -- Translating Chinese martial arts for a global audience: A multimodal perspective -- A Survey of English Translations of Jin Yong's Wuxia Fiction and Relevant Research.-Translation of Chinese Martial Arts: Principles and Methods -- Translating Shendiao Yingxiong Zhuan: A Dialogue between Two Translators -- Neural machine translation systems and Chinese martial arts movies: Moving into uncharted territory -- When Chinese Martial Artists Meet Western Heroes: A Stylometric Comparison of Translated Wuxia Fiction and Western Heroic Literature. .s
Keywords: Translating and interpreting; Intercultural communication; Fiction; Literary form; Language Translation; Intercultural Communication; Fiction Literature; Literary Genre